Civic Intelligence Oversight: Practitioners' Perspectives in France, Germany, and the UK - Sarah Naima Roller; Thorsten Wetzling; Ronja Kniep; Felix Richter (Surveillance & Society, 2023)
In recent years, various revelations about government malfeasances have highlighted the vulnerability of civil society actors who work on surveillance by intelligence agencies. Simultaneously, new technologies and overburdened state oversight bodies clarify how relevant citizen scrutiny of intelligence is. Both of these factors have led to the emergence of scrutiny by civil society actors as a research subject. This paper contributes to such scholarship by presenting data collected through surveys addressed at journalists and professionals from civil society organisations (CSOs) in France, Germany, and the UK to comparatively characterize the forms, scope, and constraints of the scrutiny they perform. Indicated differences across countries highlight variances in the practices of civic intelligence oversight. These variances indicate that there is room to manoeuvre for civic forms of holding intelligence agencies to account, counteracting the primacy of security and the secrecy of intelligence. Yet, similarities of civic oversight practitioners' perspectives across all three countries are also distinct and informative; in particular, across all three countries, journalists and CSO professionals who work on surveillance by intelligence agencies worry they are under surveillance themselves and express dissatisfaction with safeguards at work. ~
Keywords: 330; Civil Society; Oversight; Intelligence Agencies; Europe